Hybrid economy in the digital age: The case of the independent music community in Korea - Burnes, Bernard; Choi, Hwanho (Technology in Society, 2021)
The Internet is creating an increasing number of virtual communities and organisations. For many people, these virtual spaces are more real and important to them than anything in the physical world. The nature of these virtual communities and the way they are changing the relationship between market and non-market forms, are the focus of this article. As our study of the independent music scene in South Korea will show, fans have created their own virtual community, which has developed powerful non-market practices that coexist with and influence existing market practices to create a new, hybrid economic mechanism. To understand how this apparently chaotic and unregulated hybrid economic mechanism operates, we draw on studies of digital economy. This perspective seeks to understand hybridity in the economy and widespread participation and power equalisation as core factors in the development of virtual communities.
Keywords: Core factors; Digital age; Digital economy; Economic mechanisms; Equalisation; Physical world; Virtual community; Virtual spaces; Commons-based peer production; Consumer community; Digital economy; Hybrid economy; Independent music; South Korea; Virtual community